The Effect of Product Quality and Service Quality on Customer Satisfaction at Kopi Tuku in Cempaka Putih - Hazhiyah Pinggala Condroningtyas; Teguh Santoso (Golden Ratio of Mapping Idea and Literature Format, 2026)
This study aims to analyze the influence of product quality and service quality on customer satisfaction at the Cempaka Putih branch of Kopi Tuku. The study used a quantitative approach with a survey method involving 70 customers selected as respondents. Data were collected via a questionnaire and analyzed using validity and reliability tests, classical assumption tests, multiple linear regression, t-tests, F-tests, and the coefficient of determination with the aid of IBM SPSS Statistics. The results indicate that product quality and service quality have a positive and significant effect on customer satisfaction, both partially and simultaneously. Product quality is the variable with the most dominant influence compared to service quality. The coefficient of determination (R²) value of 0.731 indicates that 73.1% of the variation in customer satisfaction can be explained by these two variables, while 26.9% is influenced by other factors outside the scope of this study. These findings provide practical insights for Kopi Tuku’s management in establishing strategies for the continuous improvement of product and service quality to enhance customer satisfaction, as well as enrich the literature on factors influencing customer satisfaction in the coffee shop industry.